De novo, high-quality assembly and annotation of the halophyte grass Aeluropus littoralis draft genome and identification of A20/AN1 zinc finger protein family - Walid Ben Romdhane; Rania Ben Saad; Emmanuel Guiderdoni; Ahmed Abdelrahim mohamed Ali; Mohamed Tarroum; Abdullah Al-Doss; Afif Hassairi (BMC Plant Biology)
Abstract Background Aeluropus littoralis is considered a valuable natural forage plant for ruminant livestock and is highly tolerant to extreme abiotic stresses, especially salinity, drought, and heat. It is a monocotyledonous halophyte, has salt glands, performs C4-type photosynthesis and has a close genetic relationship with cereal crops. Moreover, previous studies have shown its huge potential as a reservoir of genes and promoters to understand and improve abiotic stress tolerance in crops. Results The sequencing and hybrid assembly of the A. littoralis genome (2n = 2X = 20) using short and long reads from the BGISeq-500 and PacBio high-fidelity (HiFi) sequencing platforms, respectively. Using the k-mer analysis method, the haploid genome size of A. littoralis was estimated to be 360 Mb (with a heterozygosity rate of 1.88%). The hybrid assembled genome included 4,078 contigs with a GC content of 44% and covered 348 Mb. The longest contig and the N50 values were 5.1 Mb and 133.77 kb, respectively. The Benchmarking Universal Single Copy Ortholog (BUSCO) value was 91.1%, indicating good integrity of the assembled genome. The discovered repetitive elements accounted for 90.6 Mb, representing 26.03% of the total genome, and included a significant component of transposable elements (11.48%, ~40 Mb). Using a homology-based approach, 35,147 genes were predicted from the genome assembly. We next focused our analysis on the zinc-finger A20/AN1 gene family, a member of which (AlSAP) was previously shown to confer increased tolerance to osmotic and salt stresses when it was over-expressed in tobacco, wheat, and rice. Here, we identified the complete set of members of this family in the Aeluropus littoralis genome, thereby laying the foundation for their future functional analysis in cereal crops. In addition, the expression patterns of four novel genes from this family were analyzed by qPCR. Conclusion This resource and our findings will contribute to improve the current understanding of salinity tolerance in halophytes while providing useful genes and allelic variation to improve salinity and drought tolerance in cereals through genetic engineering and gene editing, respectively.